Studi Transfer Massa pada Proses Dehidrasi Osmosis Kentang(Solanum tuberosum L.). - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Study on osmotic dehydration was performed by soaking potato slices into high concentrated sodium chloride solution at certain temperature. The osmotic process was observed at temperatures of 30, 40 and 50Â°C and osmotic solution concentrations of IS, 20 and 25%. The aims of this study were finding out the rate of mass transfer of water from the slices to the osmotic solution and also observing the effect of temperature and osmotic solution concentration on the mass transfer rate. The results revealed that osmotic dehydration had the same characteristic as conventional drying process at high temperature. The water removal from potato slices into the osmotic solution increased with increasing osmotic period Mass transfer of water from the slices into osmotic solution was modelled by a simple mathematical model based on Fick's and Van't Hoff laws. Increasing temperature and osmotic solution concentration enhanced the rate of water permeation. The specific permeability of potato cell walls (P,,./Lâ) and effective diffusivity of water (De) were important parameters significantly affecting the rate of water removal by osmotic dehydration.